The Relationship Between Maternal Knowledge of Exclusive Breastfeeding and Stunting Incidence Among Children Aged 12-59 Months - Alfajri, Ridho Fadila; Fitriangga, Agus; Rachmadi, Fidi (Universitas Tanjungpura, 2025)
Background: Stunting remains a major public health challenge, influenced by multiple factors including maternal knowledge about exclusive breastfeeding. Understanding this relationship is essential for improving child nutritional outcomes. Objective: To determine the association between maternal knowledge of exclusive breastfeeding and the incidence of stunting among children aged 12-59 months in the working area of Saigon Community Health Center, Pontianak. Methods: A cross-sectional study was conducted involving 48 children aged 12-59 months. Maternal knowledge was assessed using a structured questionnaire and categorized into low, moderate, and high levels. Child height was measured using standardized anthropometric procedures, and height-for-age z-scores (HAZ) were calculated using WHO Growth Standards. Stunting was defined as HAZ < -2 SD. Data were analyzed using the Chi-square test with a significance level of α = 0.05. Results: Of the 48 children, 46 were classified as stunted. The Chi-square test indicated no statistically significant association between maternal knowledge of exclusive breastfeeding and stunting incidence (p = 0.203). Conclusion: Maternal knowledge regarding exclusive breastfeeding was not significantly associated with stunting in this study population. Further research with larger sample sizes and multivariate analysis is recommended to explore additional contributing factors.